Flexural behavior of ungrouted post-tensioned concrete masonry beams with unbonded bars. (10th April 2019) - García, John M.; Bonett, Ricardo L.; Schultz, Arturo E.; Carrillo, Julian; Ledezma, Christian
Highlights: Flexural behavior of ungrouted and post-tensioned masonry beams is assessed. Behavior of ungrouted and grouted post-tensioned masonry beams was similar. US and Canadian codes predicted accurately the flexural capacity of the specimens. Performance of specimens is mainly affected by masonry compressive strength. Increase of masonry strength augmented load and displacement capacity at peak load. Abstract: Precast and post-tensioned systems increase the efficiency of masonry beams in terms of labor and time of construction. This study is aimed at evaluating the flexural behavior of ungrouted post-tensioned concrete masonry beams, with eccentric bars, and the effect of the main design parameters on their structural performance when subjected to monotonic and unidirectional cyclic loading until failure. All beams failed in flexure by crushing of the masonry in the compression region. Masonry strength was the design parameter that had the most significant effect on the load-deflection behavior of post-tensioned masonry beams. The test results showed that the measured nonlinear load-deflection behavior and the correlation between bar stress increase and midspan deflection can be estimated using a multi-linear relationship. Beams tested under monotonic and unidirectional cyclic loading exhibited comparable load-deflection envelope response.